Optimizing flow, strength, and durability in high-strength self-compacting and self-curing concrete utilizing lightweight aggregates - Kadhar, Syed Abdhaheer; Gopal, Elangovan; Sivakumar, Vivek; Anbarasu, Naveen Arasu (Matéria, 2024)
ABSTRACT This comprehensive study undertaken to investigate the properties and performance of M60 grade self-compacting and self-curing concrete mix designs. The research involved an in-depth analysis of various concrete compositions labeled as M1 to M16, each with specific aggregate combinations and percentages. The primary focus was on assessing critical properties such as flow-ability, mechanical, durability and micro structural properties. The mix labeled as M6, featuring a balanced incorporation of fine aggregate alternatives (FAA) and natural coarse aggregates (NCA), exhibited noteworthy behavior in terms of the evaluated properties. This indicated the potential advantages of judiciously combining different types of aggregates to achieve desired concrete characteristics. The research underscored the critical role of aggregate selection and substitution in determining the overall durability, strength, and structural performance of M60 grade concrete. These findings contribute to an improved understanding of optimizing concrete mix designs for achieving enhanced mechanical properties, micro structural and long-term structural sustainability. The mix M12 is more superior compared to all the mix in the form of fresh concrete properties, mechanical properties and durability properties of concrete. This study’s outcomes have implications for the construction industry, offering valuable insights into formulating concrete blends tailored for specific structural requirements and desired performance outcomes.